Efficient molecular markers for screening wheat grain arabinoxylan content (dietary fiber) developed - CGIAR Research Program on Wheat (2020)
After performing analysis, a significant genomic region located on the long arm of chromosome 1B was identified and the most significant Genotyping by Sequencing (GBS) markers identified from the Genome-Wide Association Studies (GWAS) analysis had been converted into KASP (Kompetitive allele specific PCR (Polymerase Chain Reaction)) markers. Data is published.